Right mandibular angle and left comminuted mandibular body fractures stabilised with a combination of an acetabular plate and secured pin intermandibular ventral epoxy resin (SPIVER) frame in a four‐month‐old puppy. Issue 3 (9th July 2020) - di Virgilio, Fabrizio; Bourbos, Alexandros; Cinti, Filippo; Pisani, Guido
SUMMARY: This case report aimed to describe a surgical technique combining a secured pin intermandibular ventral epoxy resin (SPIVER) frame and an acetabular plate to manage a complex mandibular fracture configuration in a puppy. A four‐month‐old, entire male, German wirehaired pointer was referred for assessment of a combination of recent (three days before hospitalisation) and older traumatic (45 days before hospitalisation) facial injuries inflicted by the dam. CT revealed multiple mandibular and maxillary fractures with complex acute mandibular fractures requiring surgical stabilisation. wo techniques were combined on stabilisation of the mandible: a single acetabular plate 2.7 to repair the mandibular angle fracture and a SPIVER frame to repair the comminuted mandibular fracture. Both fractures healed uneventfully, and the dog had normal jaw function one year postoperatively. Occlusion was not modified compared with the preoperative condition, considering that the patient already had a malocclusion defect due to old lesions. The combination of two different osteosynthesis techniques had satisfactory short‐term and long‐term outcomes in this puppy.